Pediatric Myringoplasty using the Periosteum: An Institutional Overview - Awad, Al Hussein; Hamed, Mahmood A. (International Archives of Otorhinolaryngology, 2024)
Introduction Myringoplasty is a common otologic procedure to restore the integrity of the tympanic membrane in cases of traumatic or pathologic perforations. Many grafting materials have been used with different techniques.Objective In the present work, we evaluate the surgical and audiological outcomes of periosteal graft overlying the mastoid cortex through a retroauricular incision in a pediatric cohort.Methods A retrospective study was carried out involving all children aged ≤ 16 years who underwent periosteal graft myringoplasty for the treatment of chronic suppurative otitis media with dry central perforation in our hospital from April 2019 to April 2021. All patients were followed up for one year to assess the anatomical success and functional outcomes by comparing the preoperative and postoperative (after six months) results of pure tone audiometry (PTA).Results The sample was composed of 36 patients; 20 of them were female (55.6%) and 16 were male (44.4%) subjects, with ages ranging from 7 to 16 (mean: 12.7) years. Four patients underwent surgery in both ears (with an interval of 6 to 9 months). Out of 40 surgeries performed, 38 ears have shown anatomical success (95%). A highly significant improvement in hearing was obtained (the mean difference between the pre- and postoperative results of the PTA was of 14.6 ± 3.45 dB (p < 0.001).Conclusion We advocate the use of periosteal graft in the pediatric population as a good alternative for other types of grafts, with comparable and even better functional and anatomical outcomes.
Keywords: periosteum; middle ear; myringoplasty; otitis media; outcomes